Enhancing Learning Process by Applying Cooperative Learning Supported with Augmented Reality Environment - Omari, Wael Al; Mai, Neo; Hin, Hew Soon; Hawamleh, Ahmed Al (International Journal of Membrane Science and Technology, 2023)
This study aims to examine the influence of Augmented Reality (AR) on Cooperative Learning (CL) and Students' Achievement (SA) within the context of education. This study employed a survey-based research design to investigate the proposed connections between constructs, using a two-step methodology to empirically examine the hypothesized relationships. The data collection process involved the creation of a meticulously designed, structured questionnaire, specifically targeting students at the Institute of Public Administration in KSA. A pilot test was conducted with the assistance of three experienced instructors, and a remarkable response rate of 67% was achieved with 81 completed questionnaires, of which 67 were deemed usable for analysis. To test the hypothesized associations, the cutting-edge partial least squares (PLS) modeling approach was employed, ensuring accurate and reliable results. The learning process begins with teachers explaining the new learning process and students being grouped based on cooperative learning strategies. Students will be asked to install the ARLOOPA application on their mobile devices and given printed cards to scan with their mobile devices. The findings provide compelling evidence supporting the hypotheses, indicating that the use of AR has a positive effect on both CL and SA. Furthermore, the study confirms the reciprocal relationship between CL and SA, suggesting that CL implementation fosters improved student achievement. Overall, this study contributes to the existing literature and provides valuable insights into the application of AR to enhance cooperative learning and student achievement.